Ð Ð°Ð·Ñ€Ð°Ð±Ð¾Ñ‚ÐºÐ° ÑÐ¿Ð¾ÑÐ¾Ð±Ð° ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð²Ð¸Ñ€ÑƒÑÐ° Ð±Ð¾Ð»ÐµÐ·Ð½Ð¸ ÐœÐ°Ñ€ÐµÐºÐ° - Stegniy, M. Yu.; Stegniy, B. T.; Goltsev, A. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
The cryopreservation method, consisting in application of two-stage freezing regimen down to -30°C with 1°C/min rate, from –30 down to –70°C with 5–10°C/min rate with following plunging into liquid nitrogen (–196°C) at that composition of protective media 199 nutrient media 80% with adding of inactivated serum of cattle blood 10% and dimethyl sulfoxide 10% has been developed for Marek’s disease virus.